2020
DOI: 10.1002/adsc.201901433
|View full text |Cite
|
Sign up to set email alerts
|

A 6π Azaelectrocyclization Strategy towards the 1,5,9‐Triazacoronenes

Abstract: We present the instance of two aromatic double bonds and an imine double bond involved thermal 6π-azaelectrocyclization and, on this basis, a one-step synthesis of triazacoronenes (TACs) from triphenylene-1,5,9-triamines and aldehydes under nonacidic conditions. This method has several advantages such as simplicity, high yields, and extensive substrate scope. A plausible reaction mechanism has been proposed with several experimental supports. A typical derivative shows a unique dimer holding together via a π-π… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…However, arynes have not been well-explored in the area of C–H activation because of their high reactivity, making this strategy very interesting but also very challenging . Stimulated by our recent findings on the palladium-catalyzed C–H functionalization/annulation reaction of N -alkoxybenzsulfonamides with arynes to produce tricyclic dibenzosultams and our continued interest in the synthesis of polycyclic aromatic hydrocarbons (PAHs), we envisaged that tricyclic dibenzothiazines could be prepared from sulfoximines and aryne precursors through a C–H/N–H functionalization and cyclization strategy (Scheme d).…”
mentioning
confidence: 99%
“…However, arynes have not been well-explored in the area of C–H activation because of their high reactivity, making this strategy very interesting but also very challenging . Stimulated by our recent findings on the palladium-catalyzed C–H functionalization/annulation reaction of N -alkoxybenzsulfonamides with arynes to produce tricyclic dibenzosultams and our continued interest in the synthesis of polycyclic aromatic hydrocarbons (PAHs), we envisaged that tricyclic dibenzothiazines could be prepared from sulfoximines and aryne precursors through a C–H/N–H functionalization and cyclization strategy (Scheme d).…”
mentioning
confidence: 99%
“… 11 Under optimized conditions ( Scheme 10 ), a wide variety of TAC derivatives ( 10.2 ) could be synthesized, with yields reaching 94%. 11 Acid-catalyzed conditions were used by Coskun et al to synthesize conjugated microporous polymers (CMPs) 10.6 from 1,5,9-triaminetriphenylene 10.1 and terephthalaldehyde. 12 The optical band gap and surface area of the resulting CMPs were found to correlate with the strength of the acid catalyst.…”
Section: Coronenoidsmentioning
confidence: 99%
“…[5][6][7][8] Doping of heteroatoms in aromatic rings is an effective approach for modulating physico-electrochemical properties, and several synthetic studies of heterocoronenes have been reported. [9][10][11][12][13][14][15][16][17][18][19][20] As a coronene analogue containing amide linkages, the synthesis 17 and application to organic semiconductors 18 of a D 2h symmetric compound 1 have been reported. Recently, our group has synthesized 2, a new C 3 symmetrical coronene analogue with three peripheral amide linkages, by the cyclic trimerization of 2-bromo-4-(isobutylamino)benzoic acid, followed by palladium-mediated intramolecular biarylation.…”
Section: Introductionmentioning
confidence: 99%